Applied Biophysics: A Molecular Approach for Phisical Scientists - Waigh T. A. Tom (Hoboken, John Wiley & Sons, Ltd., 2008)
This text presents a 'nuts and bolts' approach to the topic of biophysics. The presentation focuses on the simple underlying concepts and demonstrates them using a series of up-to-date applications.The book aims to explain the constructions and machinery of biological molecules, in a similar way as a civil engineer would examine the construction of a building or a mechanical engineer would examine the dynamics of a turbine. Little or no recourse is taken to the chemical side of the subject, instead modern physical ideas are introduced to explain aspects of the phenomena that are confronted. These ideas provide an alternative complementary set of tools to solve biophysical problems.The book begins with a discussion of the biological building blocks and the mesoscopic forces that occur between them. It then moves on to discuss such aspects as phase transitions, liquid crystallinity, motility, self-assembly and surface phenomena. The author then applies these principles to the behaviour of biomacromolecules, charged ions, polymers, and membranes. Furthermore applications in continuum mechanics, chromosomal structure, biorheology and modern experimental techniques are explored. Each chapter concludes with tutorial questions to challenge the reader as they progress through the text.It is hoped that the approach taken within this text will appeal to physical scientists at all levels who are confronted with biological questions for the first time, as they become involved in the current biotechnological revolution.